2009
DOI: 10.1080/07408170801958913
|View full text |Cite
|
Sign up to set email alerts
|

The impact of customer impatience on production control

Abstract: Most analyses of make-to-stock production control assume that either all orders are eventually met (complete backordering) or that no customers are willing to wait (lost sales). We consider a more nuanced model of customer behavior, where the fraction of potential customers who place orders depends on the current backlog, and hence the lead time. A continuous one-part-type, single machine model with Markov modulated demand and deterministic production is considered. We show that the impact of customer impatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Finally, we find the optimal hedging point numerically and evaluate the system performance measures including throughput (actual production rate), fill rate, and average backlog. Further analysis is given in Veatch (2007), where it is shown that the impact of B() on system performance can be expressed through a single parameter.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we find the optimal hedging point numerically and evaluate the system performance measures including throughput (actual production rate), fill rate, and average backlog. Further analysis is given in Veatch (2007), where it is shown that the impact of B() on system performance can be expressed through a single parameter.…”
Section: Overviewmentioning
confidence: 99%
“…While other functions satisfying (1) could be studied, our numerical results suggest that there is limited sensitivity to the exact shape of B(x). Furthermore, it is shown in Veatch (2007) that the impact of B(x) on system performance, for a given demand and production model, can be expressed through a single parameter. Thus, simple parametric forms of B(x) are appropriate.…”
Section: Other Performance Measuresmentioning
confidence: 99%